Nurses’ Knowledge of Palliative Care in the Pneumological Hospital - Inarvis Medina González; Elicerio Jorge Chacón Reyes; Odalys Tomaida Hernández Quintero (Medisur)
Background: application of palliative care to patients with chronic respiratory conditions is a current problem related to the quality of nursing care provided to them. Objective: to identify the nurses’ level of knowledge of palliative care for patients with chronic respiratory conditions in the Pneumological Hospital. Methods: a descriptive study was conducted in the Pneumological Hospital from January through May 2014. It included 33 nurses who provide care to hospitalized patients. The variables analyzed were years of experience, educational level, knowledge of defining aspects of palliative care, pain management, intervention for control of dyspnea, criteria for drug administration and choice of route of administration as well as nurses’ perception of their knowledge of palliative care. Results: thirty percent have more than 30 years of professional work experience, 51% are graduates. Fifty four point five percent consider that palliative care should not be provided at home; 63.6% believe that they should not be provided to patients with chronic non-cancerous diseases in advanced stages; 69.9% suggest that mixed therapies should not be used for pain management; 51.5% do not consider that breathing techniques should be used to control dyspnea. Forty eight point four percent recognize their lack of knowledge about palliative care. Conclusions: nurses from the Pneumological Hospital do not have sufficient knowledge about the different dimensions of palliative care for patients with chronic respiratory conditions.